2019
DOI: 10.1186/s12284-019-0313-y
|View full text |Cite
|
Sign up to set email alerts
|

The heterotrimeric G protein β subunit RGB1 is required for seedling formation in rice

Abstract: Background The heterotrimeric G protein β subunit RGB1 plays an important role in plant growth and development. However, the molecular mechanisms underlying the regulation of rice growth by RGB1 remain elusive. Results Here, the rgb1 mutants rgb1–1 (+ 1 bp), rgb1–2 (− 1 bp), and rgb1–3 (− 11 bp) were isolated using the CRISPR/Cas9 system, and they were arrested at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Our studies confirmed that the null mutants of RGA1 showed a severe dwarf phenotype and exhibited stress tolerance under drought, chilling, and salinity treatments. The suppression of RGB1 causes dwarfism and browning of the internodes and lamina joint regions [27], and the null mutant of RGB1 was lethal under the genetic background of ZH11 [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies confirmed that the null mutants of RGA1 showed a severe dwarf phenotype and exhibited stress tolerance under drought, chilling, and salinity treatments. The suppression of RGB1 causes dwarfism and browning of the internodes and lamina joint regions [27], and the null mutant of RGB1 was lethal under the genetic background of ZH11 [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The rgb1 mutant exhibited a semi-dwarf phenotype, and the panicle number was less than that of the WT. Sun [31,32]. However, the three base and six base deletions in rgb1-1 and rgb1-2 did not cause a frame shift, which might be the reason for the survival of rgb1-1 and rgb1-2.…”
Section: The Yield Components Of Heterotrimeric G Protein Mutantsmentioning
confidence: 93%
“…They also control many important agronomic traits in cereals (16,23,30,(36)(37)(38)(39), and understanding G-protein signaling requires a study of each subunit. Rice Gb CRISPR null mutants undergo an early developmental arrest and death, but the underlying mechanism was unclear (23,24). Here, we show that maize Gb null alleles are also lethal, and this is due to autoimmunity, not to specific developmental defects.…”
Section: Discussionmentioning
confidence: 73%
“…Maize Ga (CT2) and Arabidopsis Ga and b subunits control meristem development (16,18,25). However, the role of Gb in meristem regulation in the grasses remains obscure, because rice Gb knockouts are lethal, leading to the proposal that it is essential for growth (23,24). To study the function of maize Gb, we used CRISPR/Cas9 to generate multiple alleles, including 1bp and 136-bp deletions with premature stop codons predicted to result in null alleles ( Fig.…”
Section: Knocking Out Zmgb1 Using Crispr/cas9 Caused Lethality Due Tomentioning
confidence: 99%
See 1 more Smart Citation